From pit fire to Ultrafast High-temperature Sintering (UHS): A review on ultrarapid consolidation. Issue 3 (1st February 2023) - Kermani, Milad; Hu, Chunfeng; Grasso, Salvatore
Abstract: Extreme heating and cooling rates, approaching 10 4 °C min −1 represent a paradigm shift in materials manufacturing. In the past two decades, new techniques like Ultrafast High-temperature Sintering (UHS), and Flash sintering (FS) have emerged. Compared to conventional sintering, consolidation times are shortened by at least a thousand folds. Densification and chemical reactions proceed in a far from equilibrium condition. Readily recognized advantages of rapid sintering are suppressed grain growth, reduced loss of volatile elements (Li, Na, K), and limited interdiffusion in multi-layered devices. The accelerated kinetics opens up new opportunities to prepare ceramics with properties not attainable using slow heating rates. In the context of the current global environmental crisis, rapid sintering also holds the promise to decarbonize the sector while reducing the emissions of toxic gases associated with the firing step. This review tracks advances in rapid sintering over the past century. It examines the impact of extreme heating rates on the sintering mechanisms, and microstructural evolution throughout the three stages of sintering.